Comparison of three algorithms for initiation and titration of insulin glargine in insulin‐naive patients with type 2 diabetes mellitus (既往从未使用过胰岛素的2型糖尿病患者使用三种不同的启用与滴定甘精胰岛素剂量方案的比较). (16th September 2013) - Dailey, George; Aurand, Lisa; Stewart, John; Ameer, Barbara; Zhou, Rong
Abstract Background Several titration algorithms can be used to adjust insulin dose and attain blood glucose targets. We compared clinical outcomes using three initiation and titration algorithms for insulin glargine in insulin‐naive patients with type 2 diabetes mellitus (T2DM); focusing on those receiving both metformin and sulfonylurea (SU) at baseline. Methods This was a pooled analysis of patient‐level data from prospective, randomized, controlled 24‐week trials. Patients received algorithm 1 (1 IU increase once daily, if fasting plasma glucose [FPG] > target), algorithm 2 (2 IU increase every 3 days, if FPG > target), or algorithm 3 (treat‐to‐target, generally 2–8 IU increase weekly based on 2‐day mean FPG levels). Glycemic control, insulin dose, and hypoglycemic events were compared between algorithms. Results Overall, 1380 patients were included. In patients receiving metformin and SU at baseline, there were no significant differences in glycemic control between algorithms. Weight‐adjusted dose was higher for algorithm 2 vs algorithms 1 and 3 (P = 0.0037 and P < 0.0001, respectively), though results were not significantly different when adjusted for reductions in HbA1c (0.36 IU/kg, 0.43 IU/kg, and 0.31 IU/kg for algorithms 1, 2, and 3, respectively). Yearly hypoglycemic event rates (confirmed blood glucose <56 mg/dL) were higher for algorithm 3 than algorithms 1 (P = 0.0003) and 2 (P < 0.0001). Conclusions Three algorithms for initiation and titration of insulin glargine in patients with T2DM resulted in similar levels of glycemic control, with lower rates of hypoglycemia for patients treated using simpler algorithms 1 and 2.